Cystoid macular edema - Tryfon G Rotsos (Dove Medical Press, 2008)
Tryfon G Rotsos1, Marilita M Moschos21Medical Retina Service, Moorfields Eye Hospital, London, UK; 2Department of Ophthalmology, University of Athens, GreeceAbstract: We review the epidemiology, pathophysiology, and etiology of cystoid macular edema (CME). Inflammatory, diabetic, post-cataract, and macular edema due to age-related macular degeneration is described. The role of chronic inflammation and hypoxia and direct macular traction is evaluated in each case according to different views from the literature. The different diagnostic methods for evaluating the edema are described. Special attention is given to fluoroangiography and the most modern methods of macula examination, such as ocular coherence tomography and multifocal electroretinography. Finally, we discuss the treatment of cystoid macular edema in relation to its etiology. In this chapter we briefly refer to the therapeutic value of laser treatment especially in diabetic maculopathy or vitrectomy in some selected cases. Our paper is focused mainly on recent therapeutic treatment with intravitreal injection of triamcinolone acetonide and anti-VEGF factors like bevacizumab (Avastin), ranibizumab (Lucentis), pegaptamid (Macugen), and others. The goal of this paper is to review the current status of this treatment for macular edema due to diabetic maculopathy, central retinal vein occlusion and post-cataract surgery. For this reason the results of recent multicenter clinical trials are quoted, as also our experience on the use of intravitreal injections of anti-VEGF factors and we discuss its value in clinical practice.Keywords: cystoid macular edema, anti-VEGF, fluoroangiography, OCT, multifocal electroretinography